Loneliness, stress, self esteem and depression among Malaysian adolescents - Yaacob, Siti Nor; Juhari, Rumaya; Abu Talib, Mansor; Uba, Ikechukwu (Fakulti Pengurusan, Universiti Teknologi Malaysia, 2009)
The current study examined the degree of relationships between loneliness, stress and self-esteem with depression among adolescents. The respondents were 1407 secondary school adolescents aged between 13 to 17 years old from selected states in Malaysia. Data were collected by using a self-administered questionnaire. Adolescent depression was measured by Children Depression Inventory (CDI) (Kovacs, 1985) while stress was measured by Perceive Stress Scale (Cohen, 1983). Revised UCLA Loneliness Scale (Russell, Peplau, & Cutrona, 1980) measured loneliness and Rosenberg Self-Esteem Scale (Rosenberg, 1965) measured self-esteem. The findings of the study showed that loneliness, stress and self-esteem have moderate significant relationships with depression and stress emerged as the strongest predictor of adolescent depression.